Why the Discretion Mix Matters: Understanding the Transformation of Long-term Care Services - Young Jun Choi PhD; Hyejin Choi PhD (SAGE Publishing, 2019)
This study aims to extend the concept of discretion , ie, a certain degree of freedom in crucial decisions left to specific actors, to understand and examine the transformation of social care services in the era of aging and austerity. Although previous studies have reviewed and analyzed changes in care provision, they have been less concerned with who has the authority to make care decisions in the implementation process. We propose a new theoretical concept, the discretion mix , to understand the realignment of social care services beyond simply tracking institutional changes. Using a case study approach, this research investigates how the discretion mix of the Korean long-term care system has changed and the consequences of these changes; in addition, it discusses why the discretion mix can be a useful concept for analyzing the changing landscape of social care services.